Risk factors for low back pain in the Chinese population: a systematic review and meta-analysis - Qiang Li; Leyun Peng; Yiding Wang; Yonghui Yang; Zongbao Wang (BMC, 2024)
Abstract Background In China, the world's largest developing country, low back pain (LBP) is a common public health issue affecting workability. This meta-analysis aimed to systematically assess the risk factors of LBP in the Chinese population. Methods Four English language and four Chinese databases were searched, and cross-sectional studies on the risk factors for LBP in Chinese populations were identified and collected. The search timeframe covered the period from the establishment of the database to November 2023. Two researchers independently reviewed the literature, extracted the data, and evaluated the risk of bias. Begg's and Egger's tests were used to evaluate publication bias. Results Fifteen cross-sectional studies involving 86,575 people were included. Seven risk factors for LBP were identified. Six risk factors were statistically significant: Cigarette smoking (odds ratio [OR] = 1.55; 95% confidence interval [CI]: 1.15, 2.08, P = 0.004, I2 = 72%), body mass index (BMI) ≥ 28 kg/m² (OR = 4.51; 95% CI: 3.36, 6.07, P < 0.00001, I2 = 8%), female sex (OR = 1.54; 95% CI: 1.25, 1.90, P < 0.0001, I2 = 63%), vibration exposure at work (OR = 1.65; 95% CI: 1.16, 2.34, P = 0.006, I2 = 84%), working overtime (OR = 2.57; 95% CI: 1.12, 5.91, P = 0.03, I2 = 85%), and lack of exercise (OR = 2.48; 95% CI: 1.62, 3.78, P < 0.0001, I2 = 0%). One risk factor that was not statistically significant was standing for long periods (OR = 1.02; 95% CI: 0.82, 1.26, P = 0.88, I2 = 73%). Conclusions This study found that smoking, a BMI ≥ 28 kg/m², female sex, vibration exposure at work, working overtime, and lack of exercise may be risk factors for LBP in the Chinese population. Because the included studies were cross-sectional and the certainty of the evidence was very low, the results need to be interpreted cautiously. Multicentre, high-quality studies should be conducted in the future. To reduce the prevalence of LBP, the Chinese government and hospitals must develop early screening programs and implement effective preventive and interventional measures. Trial registration This study is registered in the PROSPERO database (No. CRD42023447857).